Revisiting the Reportedly Weak Value Relevance of Oil and Gas Asset Present Values: The Roles of Measurement Error, Model Misspecification, and Time-Period Idiosyncrasy - Boone, Jeff P. (The Accounting Review, 2002)
This paper investigates three potential explanations for the puzzlingly weak value relevance of oil and gas asset present values documented in prior research: measurement error, model misspecification, and time-period idiosyncrasy. I operationally define the magnitude of measurement error as the measurement error variance, estimated using an errors-in-variables two-stage regression model similar to that used by Barth (1991) and Choi et al. (1997). I find that (1) measurement error in the present value measure of oil and gas assets is on average less than the measurement error in the historical cost asset measure; (2) oil and gas assets measured at present value explain significantly more across-firm and across-time variation in stock prices than do oil and gas assets measured at historical cost; and (3) model misspecification partially accounts for the puzzlingly weak reported value relevance of the present value measure in prior research.